Risk Management for 4-H Youth Development Work: Volunteers - Dale Pracht; Marilyn Norman; Kate Fogarty; Jean Hink (EDIS, 2010)
4H10.6, a 3-page fact sheet by Dale Pracht, Marilyn Norman, Kate Fogarty, and Jean Hink, is part of the Risk Management for 4-H Youth Development Work series. It explains the importance of background checks and screening to recruit 4-H volunteers and describes how to educate 4-H volunteers so that they understand risk management. Includes references. Published by the Florida 4-H Youth Development Program, August 2010.